Panoramic X-ray Radiation Exposure Safety Test at ATRO Muhammadiyah Makassar - Rusli, Muhammad (Sriwijaya Journal of Radiology and Imaging Research, 2023)
Introduction: The radiation safety protocol is an effort made to create conditions so that the dose of ionizing radiation that affects humans and the environment does not exceed the specified limit value. This study aimed to measure exposure to X-ray radiation on panoramic X-rays at ATRO Muhammadiyah Mak assar. Methods: This research was conducted at the radiology department of ATRO Muhammadiyah Makassar in December 2022. The tools and materi als that will be used in this research are dental X-ray planes, survey meters, and perspex phantom, with a thickness of 10 mm, as a substitute for organs in humans. Measurement of the radiation dose exposure in dental X-ray examinations was carried out using an exposure factor of 70 kV, 8 mA at a distance of 1 meter, 2 meters, 3 meters, and 4 meters from various directions, namely fron t, left side, right side, and back with time. Different exposure on each object. Results: The highest dose intensity value was found at 0.25 seconds with a distance of 1 meter in the forward direction with a dosing accuracy of 138.4 (µSv/h). The lowest point is at 0.17 seconds with a distance of 3 meters behind wit h a dosing accuracy of 0.89 (µSv/h) for an officer who is in the radiation field during irradiation. Conclusion: The safe distance for a radiation officer and the general public who must be in the radiation field to assist patients during an examination is 4 meters from the radiation source.